A rapid workflow for the characterization of small numbers of unicellular eukaryotes by using correlative light and electron microscopy - Tůmová, Pavla; Nohýnková, Eva; Klingl, Andreas; Wanner, Gerhard (Journal of microbiological methods, 2020)
The limited availability of biological samples hinders phylogenetic efforts to define structural differences among various biological groups. A novel workflow enabling the analysis of protists in low cell numbers by electron microscopy (EM) is described with cysts of Giardia intestinalis, a single-celled eukaryotic parasite. Correlative light and electron microscopy (CLEM) allows for the selection of individual cells and is economical in terms of time and cost. We describe a cyst purification protocol in combination with an adhesive coating for fixation and ultrathin embedding that results in excellent preservation of cell morphology. The application of advanced structural and analytical EM methods, such as high-resolution field emission scanning electron microscopy (FESEM), focused ion beam tomography (FIB/SEM), and energy-dispersive X-ray spectroscopy (EDX) analysis, is demonstrated. The workflow represents a new approach for studying the cellular and organelle architecture of rare and "difficult to culture" microorganisms.
Keywords: Workflow; Phylogeny; mikroskopie elektronová rastrovací; Eukaryota; fylogeneze; mikroskopie; průběh práce; Microscopy, Electron; Microscopy; Microscopy, Electron, Scanning; elektronová mikroskopie